Gevorg Jahukyan’s Observations on the Origin of Armenian Modal Forms - GEVORKYAN, GAYANE (Bulletin of Yerevan University B: Philology, 2021)
Gevorg Jahukyan has made important interpretations on the origin of Armenian modal forms. Having divided the history of Armenian language into periods, Jahukyan referred to the formations of verbal features at different stages of the historical development of Armenian as well as to their dialect manifestations. Jahukyan also examined the various viewpoints and interpretations relevant to modal and tense forms, he clarified very important facts for Armenian studies, made observations and some corrections.